TRANSFORMASI STRATEGI INTERNALISASI NILAI EKOLOGI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP PEMBENTUKAN HABITUS EKOLOGIS SISWA - Hujumy , Muhammad Addifaul; Jazilurrahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article aims to describe and analyze in depth the Transformation of the Internalization Strategy of Ecological Values ​​in Islamic Religious Education Learning towards the Formation of Students' Ecological Habitus at MTs. Nurul Jadid Paiton Probolinggo. This research uses a qualitative research method with a case study type. The research location is at the Nurul Jadid Paiton Probolinggo Islamic Boarding School from September to November 2025. Data collection techniques used include interviews, observation, and documentation. While data analysis in this study uses the Miles and Huberman model, namely data reduction, data presentation, and conclusion drawing. The results of this study indicate that the Transformation of the Internalization Strategy of Ecological Values ​​in Islamic Religious Education Learning on the Formation of Students' Ecological Habitus through the Integration of Ecological Values ​​in the Islamic Religious Education Curriculum, Internalization of Ecological Values ​​in Islamic Religious Education Material in the Learning Process, the Islamic Religious Education Learning Model Based on Ecological Projects, Green Madrasahs Through Tree Planting, Making and Posting Ecological Posters in the Madrasah Environment and Classrooms, Implementation of Zero-Waste Culture in the Madrasah Environment and Classrooms